REDES DE FIBRA ÓPTICA DE MONITOREO DE SALUD DE ESTRUCTURAS - González Tinoco, Juan Emmanuel (My University, 2018)
optical fibre sensors; distributed sensing; optical fibre networks; time-division multiplexing; structural health monitoring; smart structures
Keywords: optical fibre sensors; distributed sensing; optical fibre networks; time-division multiplexing; structural health monitoring; smart structures